2021
DOI: 10.2298/tsci200609314z
|View full text |Cite
|
Sign up to set email alerts
|

Study on the oxidation and heating characteristics of residual coal in goafs under different air-leakage conditions

Abstract: The spontaneous combustion of broken coal is one of the main causes for mine safety accidents in goafs. To determine the effect of different air-leakage conditions on the spontaneous combustion of leftover coal, the air-leakage passage of the goaf was designed based on the principle of Sudoku grid in an inflammable coal seam. The temperature rise during the auto-ignition oxidation of coal was studied using a self-built experimental platform. By changing the air flow rate, the laws of the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Especially, CH 4 adsorbed by residual coal will affect the chemical reaction between coal and O 2 , while the reaction between CH 4 and O 2 on the surface of high-temperature coal will accelerate the spontaneous combustion of coal and increase the risk of coal spontaneous combustion. Zuo et al [80] used a self-built experimental platform to determine the effect of different air leakage conditions on the spontaneous combustion of residual coal and obtained an exponential relationship between air supply to the working face and the spontaneous combustion of broken coal in the gob. Wang et al [81] used the particle flow numerical simulation software PFC3D to simulate the collapse of the overlying rock layer in the void area, extracted the quantitative porosity data of the void area, imported it into FLUENT software, simulated the leakage flow field in the void area, and obtained the main leakage area of the working face.…”
Section: Study On the Prevention And Control Of Fire And Explosion Risks In Gobsmentioning
confidence: 99%
“…Especially, CH 4 adsorbed by residual coal will affect the chemical reaction between coal and O 2 , while the reaction between CH 4 and O 2 on the surface of high-temperature coal will accelerate the spontaneous combustion of coal and increase the risk of coal spontaneous combustion. Zuo et al [80] used a self-built experimental platform to determine the effect of different air leakage conditions on the spontaneous combustion of residual coal and obtained an exponential relationship between air supply to the working face and the spontaneous combustion of broken coal in the gob. Wang et al [81] used the particle flow numerical simulation software PFC3D to simulate the collapse of the overlying rock layer in the void area, extracted the quantitative porosity data of the void area, imported it into FLUENT software, simulated the leakage flow field in the void area, and obtained the main leakage area of the working face.…”
Section: Study On the Prevention And Control Of Fire And Explosion Risks In Gobsmentioning
confidence: 99%
“…Li et al (2022) studied and experimentally verified the relationship between O 2 , CO and CO 2 concentrations and temperature based on a mathematical model of the temperature field. Zuo et al (2021) studied the temperature rise during the natural oxidation of coal using a selfbuilt experimental platform and analyzed the variation of oxygen consumption and exothermic intensity with coal temperature by varying different air volumes and found that the exothermic intensity increased exponentially with the increase of temperature. Zeng et al (2018) investigated the oxidative spontaneous combustion characteristics of ultra-thick coal seams in the Junggar coalfield using temperature programmed experiments and thermogravimetric analysis, and quantitatively studied many parameters, such as O 2 consumption rate, CO and CO 2 generation rate, and coal reaction activation energy.…”
Section: Introductionmentioning
confidence: 99%